Pharmacokinetics Alterations in Critically Ill Pediatric Patients on Extracorporeal Membrane Oxygenation: A Systematic Review - Sutiman, Natalia; Koh, Janine Cynthia; Watt, Kevin; Hornik, Christoph; Murphy, Beverly; Chan, Yoke Hwee; Lee, Jan Hau (Frontiers in Pediatrics, 2020)
Objectives: This study aimed to identify alterations in pharmacokinetics in children on extracorporeal membrane oxygenation (ECMO), identify knowledge gaps, and inform future pharmacology studies. Data Sources: We systematically searched the databases MEDLINE, CINAHL, and Embase from earliest publication until November 2018 using a controlled vocabulary and keywords related to “ECMO” and “pharmacokinetics,” “pharmacology,” “drug disposition,” “dosing,” and “pediatrics.” Study Selection: Inclusion criteria were as follows: study population aged <18 years, supported on ECMO for any indications, received any medications while on ECMO, and reported pharmacokinetic data. Data Extraction: Clearance and/or volume of distribution values were extracted from included studies. Data Synthesis: Forty-one studies (total patients = 574) evaluating 23 drugs met the inclusion criteria. The most common drugs studied were antimicrobials (n = 13) and anticonvulsants (n = 3). Twenty-eight studies (68%) were conducted in children <1 year of age. Thirty-three studies (80%) were conducted without intra-study comparisons to non-ECMO controls. Increase in volume of distribution attributable to ECMO was demonstrated for nine (56%) drugs: cefotaxime, gentamicin, piperacillin/tazobactam, fluconazole, micafungin, levetiracetam, clonidine, midazolam, and sildenafil (range: 23–345% increase relative to non-ECMO controls), which may suggest the need for higher initial dosing. Decreased volume of distribution was reported for two drugs: acyclovir and ribavirin (50 and 69%, respectively). Decreased clearance was reported for gentamicin, ticarcillin/clavulanate, bumetanide, and ranitidine (range: 26–95% decrease relative to non-ECMO controls). Increased clearance was reported for caspofungin, micafungin, clonidine, midazolam, morphine, and sildenafil (range: 25–455% increase relative to non-ECMO controls). Conclusions: There were substantial pharmacokinetic alterations in 70% of drugs studied in children on ECMO. However, studies evaluating pharmacokinetic changes of many drug classes and those that allow direct comparisons between ECMO and non-ECMO patients are still lacking. Systematic evaluations of pharmacokinetic alterations of drugs on ECMO that incorporate multidrug opportunistic trials, physiologically based pharmacokinetic modeling, and other methods are necessary for definitive dose recommendations. Trial Registration Prospero Identifier: CRD42019114881.